(untitled) (Bangladesh Journal of Agricultural Research, 2016)
Sixty cross combinations of SakkhorkhoraR and IR58025A were studied in the experimental field of Bangabundhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Salna, Gazipur during July 2010 to November 2010, to assess the character association & contribution of characters towards grain yield in restorer lines. The correlation study revealed that days to first flowering showed significant positive relationship with seed yield per plant at genotypic levels. Days to maturity showed significant positive relationship with number of tillers per plant at both genotypic and phenotypic level and effective panicles per plant at genotypic level. Plant height showed highly significant positive relationship with effective panicles per plant at both genotypic and phenotypic level. Path analysis study revealed that effective panicles per plant (0.2153) had the highest positive direct effect followed by days to first flowering (0.1492), plant height (0.0646), spikelet fertility status (%) (0.0242) and number of seeds per panicle (0.0241). Days to maturity, spikelet sterility status, effective panicles per plant, plant height, number of tillers per plant, number of seeds per panicle and spikelet fertility status had positive indirect effects on grain yield. So, based on the study days to first flowering, plant height, spikelet fertility status ,effective panicles per plant were identified as the important characters to be considered in the selection for improvement of aromatic rice genotypes. Bangladesh J. Agril. Res. 41(3): 387-396, September 2016